Controversial Flow Cytometry Monitoring of a Relapse Case of Pediatric T Cell Acute Lymphoblastic Leukemia: A Case Report - Popa, Delia Codruţa; Şerbănică, Andreea; Obrisca, Radu; Şerbănică, Ionut; Radu, Letiţia; Jercan, Cristina; Marcu, Andra; Bica, Ana; Asan, Minodora; Petran, Mădălina; Dragomir, Mihaela; Jardan, Cerasela; et al. (Frontiers in Medicine, 2022)
Acute lymphoblastic leukemia (ALL) is the most frequent childhood cancer with 80-85% represented by B-cell ALL and only 15% by T-cell ALL. T-Cell Acute Lymphoblastic Leukemia (T-ALL) carries a more reserved prognosis compared to B-Cell Acute Lymphoblastic Leukemia (B-ALL) in regards to response to treatment, the risk of relapse, and overall survival. Progress made in current monitoring protocols such as via flow cytometry immunophenotyping (FCM) and by PCR-based amplification of antigen-receptor genes led to improved management of patients with ALL and superior rates of survival. Nevertheless, challenges remain during occasional clinical cases. This manuscript describes a unique case of T-ALL and raises awareness of such clinical challenges. The paper presents an overview of the flow cytometry immunophenotyping at diagnosis and during treatment of a pediatric patient with T-ALL from Fundeni Clinical Institute. In this case, in spite of various therapeutic measures such as first-line chemotherapy for high-risk groups, salvage chemotherapy (FLAG), conditioning regimen (FLU-BU-TT-ATG), and stem cell transplant a chemoresistance clone continued to be present.